Posouzení informačního systému firmy a návrh změn - Krätzer, Jan (Vysoké učení technické v Brně. Fakulta podnikatelská, 2020)
Diplomová práce se věnuje tématu posouzení stávajícího stavu a návrhu změn vybrané společnosti Masarykova univerzita, který slouží jako podpůrný prvek pro zaměstnance řešící úkony zákoně povinné údržby. Posouzení stávajícího stavu informačního systému je podloženo analýzou a návrhy změn byly předloženy daným zaměstnancům, kteří mají za provoz a vývoj informačního systému odpovědnost.

This diploma thesis is focused on the appraisal of the current state and the proposal for changes of the selected company Masaryk University that serves as a supporting element for the employees who deal with the actions of legally compulsory service. The appraisal of the current state of the information system is based on the analysis; the change proposals were sumbitted to the employees who are responsible for the operation and development of the information system.
Information System Assessment and Proposal of ICT Modification
Keywords: informační systém; informační technologie; data; analýza; databáze; information system; information technology; data; analysis; database